Copeptin levels in patients with coronary artery ectasia - Yavcin, Ozkan (Interv Med Appl Sci, 2019)
BACKGROUND AND AIMS: The etiology and pathophysiology of coronary artery ectasia (CAE) has not been fully elucidated. A rapid rise in plasma copeptin has been observed in cardiovascular diseases, stroke, sepsis, and shock. This increase has diagnostic and prognostic value. The aim of this study was to investigate whether copeptin has a relationship with CAE. METHODS: This observational prospective study was carried out between October 2012 and March 2013 in the cardiology catheter laboratory with the inclusion of 44 subjects with a diagnosis of CAE and 44 age- and gender-matched individuals with normal coronary arteries. Blood samples obtained from the patients were stored at −70 °C until analysis and copeptin levels in sera were measured by ELISA. RESULTS: This study comprised 88 study participants, among whom 44 were patients meeting ectasia criteria [mean age: 58.0 ± 11.5 years; 59% (n = 26) male], and 44 were control subjects with angiographically normal coronary anatomy [mean age: 49.2 ± 10.1 years; 30% (n = 13) male]. Copeptin levels were similar between the groups (p > 0.05). In addition, there was no correlation between copeptin levels and CAE. CONCLUSION: In this study, it is examined that copeptin levels were not elevated in CAE patients.